Tributyltin Exposure Is Associated With Recognition Memory Impairments, Alterations in Estrogen Receptor α Protein Levels, and Oxidative Stress in the Brain of Female Mice - Ferraz da Silva, Igor; Merlo, Eduardo; Costa, Charles S.; Graceli, Jones B.; Rodrigues, Lívia C. M. (Frontiers in Toxicology, 2021)
Tributyltin (TBT) is a persistent organometallic pollutant widely used in several agricultural and industrial processes. TBT exposure is associated with various metabolic, reproductive, immune, and cardiovascular abnormalities. However, few studies have evaluated the effects of TBT on behavior. In the present study, we aimed to investigate whether TBT exposure results in oxidative, neuroendocrine and behavioral alterations. TBT was administered to adult female mice (250, 500 or 750 ng/kg/day or veh for 14 days), and their recognition memory was assessed. We have also evaluated ERα protein expression and oxidative stress (OS) in brain areas related to memory, as well as the correlation between them. A reduction in short- and long-term recognition memory (STM and LTM) performance, as well as in total exploration time were observed in TBT mice. Reduced ERα protein expression was observed in the prefrontal cortex (PFC) and hippocampus of TBT mice, while an increase in TBARS concentration was observed in the PFC of treated animals. Collectively, these data suggest that TBT exposure impairs recognition memory in female mice as a result of, at least in part, its toxicological effects on ERα expression and OS in specific brain areas related to memory.